Anterior pituitary gland volume mediates associations between adrenarche and changes in transdiagnostic symptoms in youth - Giorgia Picci; Nathan M. Petro; Chloe C. Casagrande; Lauren R. Ott; Hannah J. Okelberry; Danielle L. Rice; Anna T. Coutant; Grace C. Ende; Erica L. Steiner; Yu-Ping Wang; Julia M. Stephen; Vince D. Calhoun; et al. (Developmental Cognitive Neuroscience)
The pituitary gland (PG) plays a central role in the production and secretion of pubertal hormones, with documented links to the increase in mental health symptoms during adolescence. Although literature has largely focused on examining whole PG volume, recent findings have demonstrated associations among pubertal hormone levels, including dehydroepiandrosterone (DHEA), PG subregions, and mental health symptoms during adolescence. Despite the anterior PG’s role in DHEA production, studies have not yet examined potential links with transdiagnostic symptomology (i.e., dysregulation) pertinent to long-term functioning. Therefore, the current study sought examine whether anterior PG volume mediates associations between DHEA levels and changes in dysregulation symptoms in an adolescent sample (N = 114, 9 –17 years, Mage = 12.87, SD = 1.88). Following manual tracing, structural equation modeling revealed that greater anterior, not posterior, PG volume mediated the association between greater DHEA levels and increasing dysregulation symptoms across time, controlling for baseline dysregulation symptom levels. Results also showed that greater DHEA levels related to decreasing symptoms across time, suggesting potential attenuation effects. Altogether, these results provide support for separating the anterior and posterior PG by demonstrating specificity in the role of the anterior PG in adrenarcheal processes that may confer risk for adolescent psychopathology.